Analisis Kemampuan Berpikir Komputasi Matematis Siswa pada Pembelajaran Matematika - Theresia Safitri; Tiara Laura Br Ginting; Widya Indriani; Rosliana Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The aim of this research is to provide a study of the computational thinking process of mathematics learning. This research uses library research methods. The data obtained is the publication of research articles in scientific journals. Data analysis includes three stages: organize, synthesize, and identify The result of previous research is students' computational thinking abilities need to be improved in abstraction and algorithms.